Infrared Thermography Measurements over a Tail-Plane Model of a Large Passenger Aircraft. Issue 1 (1st June 2022) - Zanotti, A.; Rausa, A.; Grassi, D.; Riccobene, L.; Gibertini, G.; Guardone, A.; Auteri, F.
Abstract: In the frame of the CleanSky 2 MONNALISA project, a wind-tunnel campaign is planned to test a tail-plane model of a large passenger aircraft by using different measurement techniques. Wind-tunnel test results obtained over a systematic series of model geometries will be used to thoroughly validate a low-order numerical method based on physical modelling that will be developed in the project to evaluate the non-linear aerodynamic characteristics of aircraft lifting surfaces. The present paper describes the main results of the infrared thermography measurements performed in the first wind-tunnel entry to be used to tune RANS solvers and for the fine calibration of the low-order numerical method.